MODELLING AND CHARACTERIZATION OF INTRALAMINAR AND TRANSLAMINAR FRACTURE TOUGHNESS OF QUASI UNIDIRECTIONAL COMPOSITE - Gilbert C.W., Alexander
As technology continues to advance, especially in lightweight structural engineering, the use of composite materials in various products is becoming more common. Quasi-unidirectional composite is one example of a continuous fiber-reinforced composite. In practical use, composites can fail through deformation or cracking. Thus, knowing the fracture toughness of this material is important for predicting failures and designing more effective products. This undergraduate thesis discusses the fracture toughness caused by intralaminar and translaminar damage. The specimen used in this work is carbon/epoxy composite specimen with layup sequence of [90°]8s to analyze intalaminar damage and [90°/0°]4s to analayze translaminar damage which are studied through experimental and simulation approach. The experimental work involves designing and performing compact tension test, while the simulation is carried out using the finite element method software, Abaqus CAE. As a result, the specimen with a layup sequence of [90°]8s successfully perform crack propagation along the specimen to create intralaminar damage. It has been found out that the fracture toughness of intralaminar damage for this specimen is 6.92 N/mm and successfully simulate the damage using cohesive zone method. Meanwhile, the specimen with a layup sequence of [90°/0°]4s failed to perform crack propagation to create translaminar damage so the fracture toughness could not be analyzed. Buckling and matrix damage occurs during this compact tension experiment. Modelling using Hashin damage criterion also could not simulate complex damage that occurs in the experiment. Another output has been found out that tapered-rear model compact tension could reduces force drop from buckling effect.